PENGARUH NON PERFORMING LOAN DAN NET INTEREST MARGIN TERHADAP KINERJA KEUANGAN DENGAN CAPITAL ADEQUACY RATIO SEBAGAI VARIABEL INTERVENING PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Insani, Auliasha Firlana Hadi; Wahyuni, Ika; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aimed to determine the effect of Non Performing loans and Net Interest margins on financial performance with the Capital Adequacy Ratio as an intervening variable in the Banking Sector listed on the Indonesia Stock Exchange 2019-2021. The population in this study were all Banking Sectors listed on the Indonesia Stock Exchange in 2019-2021, totaling 47 Banks. The sampling technique for this study used purposive sampling, so that 13 samples were obtained, which were used as data analysis. Data analysis and hypothesis testing in this study used the Smart PLS 3.0 application. The results of this study indicate that Non Performing Loan has a positive but insignificant effect on Capital Adequacy Ratio, Net Interest Margin has a significant negative effect on Capital Adequacy Ratio, Non-Performing Loan has a positive but insignificant effect on Financial Performance, Net Interest Margin has a significant negative effect on Capital Adequacy Ratio. Significant to financial performance, Net Interest Margin has a negative but insignificant effect on financial performance, Capital Adequacy Ratio has a positive but insignificant effect on financial performance, Non-Performing Loan has a positive but insignificant effect on financial performance through Capital Adequacy Ratio, and Net Interest Margin has a negative but insignificant effect on financial performance through Capital Adequacy Ratio.